The Canadian federalist experiment : from defiant monarchy to reluctant republic - Vaughan, Frederick (McGill-Queen's University Press, 2003)
"The Canadian Federalist Experiment details how the fathers of Canadian Confederation, eager to perpetuate monarchical government despite Enlightenment thinkers' views that republicanism was the only legitimate form of government, embraced the Hobbesean principles of the English constitution. Monarchical principles were embedded in the Canadian constitution of 1867, leading to concentration of power in the office of the prime minister. Frederick Vaughan looks at changes that have taken place in Canada since 1867, arguing that Pierre Trudeau's 1982 Constitution Act quietly undermined the monarchic character of the constitution by introducing republican principles of government, leaving Canada clinging to the wreckage of the old aristocratic order while attempting to provide a new order founded on republican equality."--Jacket.